Correction: Attrition in serum anti-DENV antibodies correlates with high anti-SARS-CoV-2 IgG levels and low DENV positivity in mosquito vectors-Findings from a state-wide cluster-randomized community-based study in Tamil Nadu, India. - Sivaprakasam T Selvavinayagam; Sathish Sankar; Yean K Yong; Abdul R Anshad; Samudi Chandramathi; Anavarathan Somasundaram; Sampath Palani; Parthipan Kumarasamy; Roshini Azhaguvel; Ajith B Kumar; Sudharshini Subramaniam; Manickam Malathi; et al. (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003608.].